Breaking the mould: Developing innovative crop protection strategies with Reflexive Interactive Design - Moreira, Tatiana; Groot Koerkamp, Peter; Janssen, Arni; Stomph, Tjeerd-Jan; van der Werf, Wopke (Agricultural systems, 2023)
Pests and pathogens can have great impacts on agricultural production. The use of plant protection products (PPPs) is a main preventive and curative management method in conventional farming today world-wide. However, increasing evidence shows the negative effects of PPPs on the environment and human health. New, especially preventive, approaches are needed and a promising option for developing these is the redesign of current agricultural systems, in which knowledge about the system and biological processes is integrated. Yet frameworks that can guide this process are not widely used. This study aims to demonstrate the use of an innovative and systematic approach to the development of design concepts for pest and disease management without the use of PPPs, using Phytophthora infestans in potatoes as a case study. The Reflexive Interactive Design method was applied to define design goals, requirements and key functions of the innovative design. These definitions were based on the needs of relevant stakeholders and the biology of the crop and disease. A range of strategies were researched that could effectively limit pathogen transmission and disease severity by interrupting the pathogen's life cycle. The proposed design concept focuses on a combination of more traditional aspects like providing farmers with uninfected starting material and resistant varieties with novel approaches like increasing canopy porosity through intercropping with onions and preventing the spread of inoculum both into and within the field with a combination of host dilution and barriers. This research demonstrates how the Reflexive Interactive Design method can be used to develop innovative solutions for crop protection that go beyond current solution sets. The systematic approach backed by literature provided the compass for the search for new and innovative solutions with strong focus on prevention. The design concept acts as a promising starting point to be further elaborated with stakeholders while effectiveness of the final design concept needs to be tested under real-life conditions. [Display omitted] •Systematic design methods for developing novel crop protection strategies are missing.•The reflexive interactive design (RIO) method was tested for its ability to help generate novel preventive solutions.•Linking pathogen life cycle to key functions resulted in a novel crop protection concept for Phytophthora infestans.•The proposed design concept could act as a promising starting point to be further elaborated with stakeholders.•The field of crop protection can benefit from systematic design methods such as RIO to develop outside the box ideas.